Corruption and Vulnerable Employment in Relation to the Government Procurement Act during the Public Health Emergency - Ciriaco Caqui, Jeferson Jesús (2023)
This research sought to establish how corruption has violated the regulations of the Ley de Contratación del Estado during the current crisis due to the COVID-19 pandemic. Thus, the aim was to learn how corruption and the current institutional deterioration influence existing regulations regarding public procurement, considering that this process takes place in a direct manner due to the public health emergency. A qualitative approach was used in this research, with explanatory-descriptive analysis. The unit of analysis was the purchase orders made by public entities. The sample was non-probabilistic and selected through simple random sampling. The data analysis led to the conclusion that it is necessary to strengthen both the regulation factors in the direct procurement (without a public tender) from the Government and public administration such as inspection. In addition, there should be greater emphasis and dedication from the Government to take action in the prevention of corruption.